2015
DOI: 10.17722/ijme.v5i1.795
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Safety Climate on Safety Performance in a Gold Mining Company in Ghana

Abstract: The study investigated the influence of safety climate on safety performance among employees in a multi-national gold mining company in Ghana. Safety climate was conceptualized and measured in terms of employee perceptions of management value for safety, supervisor safety practices, safety communication, safety training and safety system. Safety performance was conceptualized and measured in terms of employee safety compliance and safety participation, that is, how they make suggestions to improve safety in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…All of these things will encourage members to behave more safely, where members of the organization will be more obedient in carrying out occupational safety and health regulation that has been set by an organization or company where employees work (safety compliance), and the higher employee participation in campaigning for a work safety culture and also setting a good example in terms of safety participation. The results of this study are also supported by previous research (Clarke, 2013;Jiang et al, 2013;Ismail, 2015), which states that safety behavior will be created well if the safety climate is also getting better.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…All of these things will encourage members to behave more safely, where members of the organization will be more obedient in carrying out occupational safety and health regulation that has been set by an organization or company where employees work (safety compliance), and the higher employee participation in campaigning for a work safety culture and also setting a good example in terms of safety participation. The results of this study are also supported by previous research (Clarke, 2013;Jiang et al, 2013;Ismail, 2015), which states that safety behavior will be created well if the safety climate is also getting better.…”
Section: Resultssupporting
confidence: 88%
“…(Griffin et al, 2000) states that safety compliance is the effort of workers in carrying out work procedures in accordance with work safety rules in the company. (Clarke, 2013;Ismail, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In support of the positive effect of safety culture on safety behaviour [21] indicated that team safety climate influenced proactive behaviours by increasing proactive orientation but influenced prosocial behaviours by increasing affective commitment. In a cross-sectional survey among multinational gold mining companies in Ghana investigating the influence of safety climate on safety performance, [45] found that safety climate had a positive relationship with safety performance. Meanwhile, the work of [45] actually measured safety performance with the two component safety behaviour of safety compliance and safety participation (i.e.…”
Section: Safety Culture Safety Behaviour and Safety Performancementioning
confidence: 99%
“…In a cross-sectional survey among multinational gold mining companies in Ghana investigating the influence of safety climate on safety performance, [45] found that safety climate had a positive relationship with safety performance. Meanwhile, the work of [45] actually measured safety performance with the two component safety behaviour of safety compliance and safety participation (i.e. safety behaviour in this paper).…”
Section: Safety Culture Safety Behaviour and Safety Performancementioning
confidence: 99%
“…Employee attitude and subjective norms have a positive impact on organization safety (Abdullah et al , 2016), and its emphasis on safety can effectively prevent potential damage (Yueng-hsiang et al , 2014). Second, employees’ safety behaviors can promote the improvement of enterprise safety level (Ismail, 2015; Boustras et al , 2015). Employees’ perception of safety atmosphere and their safety participation can effectively reduce the incidence of work-related injuries (Cook et al , 2016).…”
Section: Literature Reviewmentioning
confidence: 99%